Plaque Accumulation Around Ti5 3D-Printed Bar-Shaped Versus Conventional Dead-Soft Stainless-Steel Lingual Fixed Retainers: A Randomized Controlled Clinical Trial - Amany Zeinhom Ibrahim Eltantawy (Journal of Intelligent Decision Making and Information Science, 2026)
Objectives: To compare plaque accumulation between Ti5 3D-printed bar-shaped lingual fixed retainers (Group I) and conventional dead-soft stainless-steel (Retainium®) lingual fixed retainers (Group II) over 6 months following placement. Methods: A single-centre, parallel randomized controlled trial (1:1 allocation; ClinicalTrials.gov: NCT07538869) enrolled 20 post-orthodontic adults (10 per group). Plaque accumulation was assessed using the Löe Plaque Index (PI) at six mandibular anterior teeth and at four tooth surfaces (distal, mesial, buccal, lingual) at baseline (T0), 3 months (T3), and 6 months (T6). Non-parametric tests were applied; significance level p ≤ 0.05. Results: All 20 participants completed follow-up. Groups were comparable at baseline (age: p = 0.74; sex: p = 0.36). Interobserver reliability was excellent (ICC 0.947–1.000; all p < 0.0001). Overall PI was not significantly different at T3 (Group I: 0.86 ± 0.27 vs. Group II: 1.03 ± 0.31; p = 0.35); however, the lower right central incisor was already significantly lower in Group I (0.85 ± 0.32 vs. 1.23 ± 0.40; p = 0.04). By T6, overall PI was significantly lower in Group I (1.05 ± 0.26 vs. 1.42 ± 0.34; p = 0.01). Both groups showed significant PI increases from T3 to T6 (p = 0.005), with greater magnitude in Group II. Surface-specific analysis revealed a highly significant between-group difference at the lingual surface at T6 (0.75 ± 0.21 vs. 1.82 ± 0.44; p < 0.0001). Conclusions: Ti5 3D-printed bar-shaped lingual fixed retainers demonstrated significantly lower plaque accumulation compared with conventional stainless-steel retainers at 6 months, particularly at the lingual surface, supporting their adoption in patients requiring long-term fixed retention. Trial registration: ClinicalTrials.gov NCT07538869.